Literary Translation, Reception, and Transfer - Bachleitner, Norbert (XXI. Congress of the ICLA - Proceedings, 2020)
The three concepts mentioned in the title of this volume imply the contact between two or more literary phenomena they are based on similarities that are related to a form of 'travelling' and imitation or adaptation of entire texts, genres, forms or contents. Transfer comprises all sorts of 'travelling', with translation as a major instrument of transferring literature across linguistic and cultural barriers. Transfer aims at the process of communication, starting with the source product and its cultural context and then highlighting the mediation by certain agents and institutions to end up with inclusion in the target culture. Reception lays its focus on the receiving culture, especially on critcism, reading, and interpretation. Translation, therefore, forms a major factor in reception with the general aim of reception studies being to reveal the wide spectrum of interpretations each text offers. Moreover, translations are the prime instrument in the distribution of literature across linguistic and cultural borders thus, they pave the way for gaining prestige in the world of literature. The thirty-eight papers included in this volume and dedicated to research in this area were previously read at the ICLA conference 2016 in Vienna. They are ample proof that the field remains at the center of interest in Comparative Literature.